DETERMINANTS OF BOTTLE USE AMONGST ECONOMICALLY DISADVANTAGED MOTHERS - Shamim, Samina; Jamalvi, S. Waseem; Naz, Farah (Journal of Ayub Medical College Abbottabad, 2006)
Background: There is documented evidence of increased risk of infant mortality in formula fed infants versus breast fed babies. The hazards of bottle use for infant feeding, especially in underprivileged communities, are also well known. As the issue of bottle use is directly related to childhood survival and mortality, there is legislation against propagation of bottle-feeding in Pakistan. Methods: Objectives: To obtain information about determinants of bottle use for infant feeding in a low-income periurban community. Design: Community based cross-sectional study. Results: 150 mothers with infants up to one year of age were included in the study period from October 03 to March 04. Out of these 102 mothers were found using bottle for infant with or without breast-feeding. The tendency to use the bottle increased in relation to child’s increasing age. Only 17% of the infants under the age of 3 months were offered bottle, it was 69% between 4 to 6 months and it increased to 76%.in infants from 7 months to 1 year. The attributes associated with increased bottle use were mother’s older age, illiteracy and increased parity. Conclusion: Bottle use is a public health issue in poor and illiterate mothers of developing countries. While, in Pakistan, laws are enacted against its propagation, we need community-based strategies to bring about a socio-cultural shift in the growing prevalence of bottle use found in the study. Key words: Infant feeding in developing countries, bottle use, breast milk substitute.